2020
DOI: 10.1051/e3sconf/202021018096
|View full text |Cite
|
Sign up to set email alerts
|

The main criteria for the formation of communicative universal educational actions in primary school children with learning disabilities

Abstract: The article deals with the characteristic features of speech development of primary school children with learning disabilities, due to the peculiarity of the development of their cognitive activity. The main types of communicative universal educational actions are analyzed. Criteria for assessing the level of development of communicative universal educational activities in younger students with learning disabilities are highlighted. The significance of these criteria for determining the directions of correctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Due to low self-esteem and self-doubt, at the initial stages of art therapy, patients were given easier tasks available for completion, which was aimed at preventing the formation of a negative attitude to art therapy [26].…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…Due to low self-esteem and self-doubt, at the initial stages of art therapy, patients were given easier tasks available for completion, which was aimed at preventing the formation of a negative attitude to art therapy [26].…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…The first direction assumes the development of mental functions, which form the psychological basis of pupils` speech. The theoretical analysis of the research showed that students with learning disabilities have perception, attention, speech and memorydelay [10,11,12,13,14,15].These functions provide the background for successful development of communicative activity.…”
Section: Introductionmentioning
confidence: 99%
“…Every year, 20,000 children under the age of 17 are diagnosed oncology and not everyone can have a chance to recover. In the field of work with cancer patients, the processes of professional and emotional burnout are considered to be more aggravated because of the constant necessity for interpersonal interaction with patients and their relatives; continuous observing of the suffering of children [2][3][4]. So, N.L.…”
Section: Introductionmentioning
confidence: 99%